Newly detected, virulent Toxoplasma gondii COUG strain causing fatal steatitis and toxoplasmosis in southern sea otters (Enhydra lutris nereis) - Miller, Melissa Ann; Newberry, Cara A.; Sinnott, Devinn M.; Batac, Francesca Irene; Greenwald, Katherine; Reed, Angelina; Young, Colleen; Harris, Michael D.; Packham, Andrea E.; Shapiro, Karen (Frontiers in Marine Science, 2023)
Beginning in 2020, four southern sea otters (Enhydra lutris nereis) stranded in California with severe protozoal steatitis and systemic toxoplasmosis. Three of the infected otters stranded within 26 km of each other, and all four animals died during a period of increased rainfall-driven surface water runoff during February and March. High parasite burdens were observed in all tissues except the central nervous system, and toxoplasmosis with severe protozoal steatitis was the primary cause of death for all cases. This lesion pattern differs substantially from all prior reports of toxoplasmosis in sea otters. All cases were T. gondii-positive via serology, immunohistochemistry, and PCR. Multilocus sequence typing at 13 loci revealed that all were infected with the same strain of T. gondii, previously characterized as an atypical and rare genotype in North America (TgCgCa1, or COUG). The COUG genotype was first isolated from mountain lions in British Columbia, Canada during investigation of a waterborne outbreak of toxoplasmosis in humans. This genotype has not been previously reported from sea otters, nor any aquatic species. All prior T. gondii strains obtained from >140 southern sea otters represent Type II or Type X strains, or variants of these genotypes. Archival necropsy data (>1,000 animals over 24 years) were negative for prior cases of severe T. gondii-associated steatitis prior to the cases described herein, and no sublethal COUG T. gondii infections have been identified in sea otters. According to prior studies, the T. gondii COUG genotype is highly virulent in mice and is unusual among T. gondii isolates in eliciting a Type I interferon response in murine and human cells in vitro; this unusual immunomodulatory response could explain the apparent high virulence of this atypical T. gondii strain. Our findings reveal a novel and concerning lesion pattern for sea otters with toxoplasmosis. Due to high zoonotic potential and the risk of infection via shared marine food resources, these findings may also indicate potential health threats for other animals and humans.